Transplantasi Teori Reverse Piercing The Corporate Veil Dalam Perseroan Terbatas Di Indonesia - Marzha Tweedo Dikky Paraanugrah (Universitas Islam Indonesia, 2019)
The theory of reverse piercing the corporate veil is used by the United States Court to settle disputes between shareholders who use limited liability companies to save their assets in order to avoid suing individual shareholder-creditors. In the future, Indonesia needs to assess the potential application of the theory of reverse piercing the corporate veil in the country through a transplantation mechanism. This research will analyze first, the potential application of the theory of reverse piercing the corporate veil in Indonesia according to the legal transplantation theory and second the method of applying the theory of reverse piercing the corporate veil in Indonesia. This study uses the normative legal research method. The conclusion of this research is firstly, based on the legal transplant theory popularized by Watson, the theory of reverse piercing the corporate veil has the potential to be transplanted in Indonesia. The transplant is based on the existence of legal equality between the United States and Indonesia with limited liability company law. Secondly, the method of implementing reverse piercing in Indonesia adopts the same method as the United States of America, which is reversing the parameters that exist in piercing the corporate veil.